Presence and habitat use of the endangered Bornean elephant (Elephas maximus borneensis) in the INIKEA rehabilitation project site (Sabah, Malaysia) : a pilot study - Crespo Mingueza, Laia (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2018)
The endangered Bornean elephants (Elephas maximus borneensis) are endemic to the island of Borneo and their survival is being threatened by palm oil production, poaching and human-elephant conflicts. In Central Sabah (Malaysia), the conversion of forests into commercial plantations has led to habitat fragmentation and human-elephant conflicts. The present pilot study aimed to assess the suitability of a protected forest reserve in Central Sabah (INIKEA Forest Rehabilitation project site) for elephants, assess elephant distribution at the site and document the presence of other terrestrial mammals. This was done using a combination of wildlife surveys. The potential role of this forest reserve in wildlife management and conservation is as well discussed.